A Novel and Efficient Synthesis of δ-Sultones - Rad-Moghadam, Kurosh; Roudsari, Saeedeh Toorchi; Sheykhan, Mehdi (Synlett, 2014)
A class of sulfonic ionic liquids, with the supremacy of methylsulfonylimidazolium triflate hydrochloride, was found to be efficient for catalyzing the self-condensation of acetophenone derivatives and sulfonating the resulting condensates in a one-pot rapid reaction leading to the synthesis of 4,6-diaryl-1,2-oxathiine-2,2-dioxides (diaryl-δ-sultones).
Keywords: δ-sultone; ionic liquid; sulfonation; domino reaction; oxathiine-2,2-dioxide